Development of a survey instrument for measuring workers satisfaction on usability of manual handling equipments at the warehouse: a pilot study - Abdul Rahman, Ismail; Azis, Noorul Azreen; Mahmood, Salwa; Mohd Rohani, Jafri; Zaidi, Nor Amira Farhana; Mohd Sukri, Suhaimi; Mohd Zain, Mohd Arif Afzan (2022)
Scientific evidence show that manual handling devices are one of the effectives controls that can lower the physical demands of manual material handling (MMH) activities. Incidence and severity of the musculoskeletal injuries might happen to workers while company’s productivity, product quality, and overall business competitiveness also will be affected. However, few studies had been done regarding on manual handling devices provided in the industries especially in term of user satisfaction on the usability of the devices when performing their job and task. The aim of this study is to develop a survey instrument for the evaluation of worker satisfaction on usability of manual handling device among warehouse worker in manufacturing industry. A set of questionnaires was developed which consist of three sections; demographic profile of respondent, work nature and discomfort survey and worker satisfaction on the usability of the manual handling devices. The content of the questionnaire was derived through extend literature reviews and expert’s opinions. A pilot study was conducted at four manufacturing companies in their warehouse’s operation. The reliability and validity of the instrument were determined through Cronbach’s Alpha, face validity and content validity. Cronbach’s Alpha values for each section of the questionnaire range from 0.937 and 0.961 while the value for Cronbach’s Alpha for all 35 standardized items is 0.921. The finding shows that the survey instrument has face and content validity at acceptable level. In conclusion, finding indicated that this instrument had acceptable and adequate reliability and validity to meet its objectives. The survey instrument now ready to be distributed in larger data sets.